Electronic Patient‐Reported Outcome Quality of Life Score in Japanese Patients With Pancreatic Cancer on Second‐Line Chemotherapy: A Multicenter Observational Study - Yuki Takumoto; Akihiro Ohba; Takeshi Terashima; Makoto Ueno; Kenji Ikezawa; Naohiro Okano; Takuji Okusaka; Chigusa Morizane; Masafumi Ikeda; Masato Ozaka; Hiroto Narimatsu; Manabu Akazawa; et al. (Cancer Medicine)
ABSTRACT Introduction Patients' QoL scores during chemotherapy are generally measured during hospital visits. However, patients frequently recover from AEs before hospital arrival. This study continuously assessed each chemotherapy's impact on patients' QoL scores during hospital visits and at home using an electronic device (ePRO). Methods This multicenter, prospective observational study was conducted in 29 Japanese hospitals. Patients were treated with liposomal irinotecan, fluorouracil, and levoleucovorin (Nal‐IRI + 5‐FU/LV), gemcitabine and nab‐paclitaxel (GnP), or gemcitabine (GEM) as second‐line chemotherapy for unresectable pancreatic cancer. All respondents used ePRO to answer several QoL questionnaires on Days 1, 2, 4, 6, 8, and 11 following chemotherapy administration. The primary endpoint was the EQ‐5D‐5L index value, and the secondary endpoints were AE frequency and the EORTC QLQ‐C30. Results The analysis included 67 participants. The mean ± SD QoL scores of the Nal‐IRI + 5‐FU/LV and GnP arms varied from 0.803 ± 0.142 to 0.678 ± 0.247 and 0.872 ± 0.077 to 0.726 ± 0.185, respectively, over the evaluation period. The highest and lowest QoL scores were observed around the chemotherapy administration and approximately 1 week after the chemotherapy administration, respectively, in both arms. Conclusions Patients' QoL score assessment over time by ePRO revealed QoL score trends, which emphasized the importance of QoL management outside of hospital visits for each chemotherapy.